(untitled) (Annals of Bangladesh Agriculture, 2020)
An investigation was carried out to study the genetic parameters and character association for yield, yield attributing, quality and nutritional traits of twelve rice varieties. Analysis of variance revealed significant differences for all the traits under study indicated the presence of wide genetic variability among the genotypes. Small differences between genotypic coefficient of variation and phenotypic coefficient of variation were recorded for all the characters studied which indicated less influence of environment on these characters. High heritability coupled with high genetic advance was observed for zinc content (brown) and number of chaffy grain per panicle exhibited, indicating that simple selection could be effective for improving these characters. Yield per hill had the highest positive direct effect. This study revealed that yield per hill, days to 50% flowering, days to maturity, panicle length and thousand grain weight are the most important yield contributing characters and an attempt should, therefore, be made for effective selection on these traits. Yield per hill might be considered as the most important trait due to low difference of GCV and PCV, high heritability in broad sense (h2b) with high genetic advance (GA) in percent of mean, significant positive correlation and high positive indirect effects. Another important trait such as days to 50% plants to flowering and thousand grain weight might also be considered due to their minimum difference of GCV and PCV values, high h2b with high GA in percent of mean, significant positive correlation and higher positive direct effects. Ann. Bangladesh Agric. (2019) 23(1) : 69-77